THE IMPACT OF INCREASING COOKING OIL PRICES ON FOOD CONSUMPTION PATTERNS IN VARIOUS HOUSEHOLD INCOME GROUPS IN ACEH PROVINCE - Mawardati; Jullimursyida; Azhar; Iga Mayada; Eva Juwita (CV. Radja Publika, 2023)
Consumption of cooking oil from year to year continues to increase, especially in Aceh Province. In general, almost all people in this area consume cooking oil derived from oil palm plants for household needs. As one of the basic needs, the increase in the price of cooking oil has affected changes in household consumption patterns. This study aims to analyze the impact of rising cooking oil prices on changes in people's food consumption patterns in various household income groups in a quantitative descriptive manner. The results of the analysis show that the increase in the price of cooking oil has an impact on changes in food consumption patterns, namely a decrease in consumption of several food needs other than cooking oil. This decline occurred in various household income groups in Aceh Province.